Hollywood and whine the snippy, snotty, and scandalous things stars say about each other - Hadleigh, Boze
When sex kittens turn catty and star let their updos down--LOOK OUT! This lowdown collection reveals what celebrities say frankly about each other and themselves when they're wondering whether all their gain is worth the pain.